Evaluating immunity to SARS‐CoV‐2 in nursing home residents using saliva IgG. Issue 3 (22nd January 2022) - Katz, Morgan J.; Heaney, Christopher D.; Pisanic, Nora; Smith, Leigh; Bigelow, Benjamin F.; Sheikh, Fatima; Boudreau, Alec; Kruczynski, Kate; Hsu, Yea‐Jen; Salinas, Alejandra B.; Cosgrove, Sara E.; Rock, Clare
Abstract: Background: SARS‐CoV‐2 circulating variants coupled with waning immunity pose a significant threat to the long‐term care (LTC) population. Our objective was to measure salivary IgG antibodies in residents and staff of an LTC facility to (1) evaluate IgG response in saliva post‐natural infection and vaccination and (2) assess its feasibility to describe the seroprevalence over time. Methods: We performed salivary IgG sampling of all residents and staff who agreed to test in a 150‐bed skilled nursing facility during three seroprevalence surveys between October 2020 and February 2021. The facility had SARS‐CoV‐2 outbreaks in May 2020 and November 2020, when 45 of 138 and 37 of 125 residents were infected, respectively; they offered two Federal vaccine clinics in January 2021. We evaluated quantitative IgG in saliva to the Nucleocapsid (N), Spike (S), and Receptor‐binding domain (RBD) Antigens of SARS‐CoV‐2 over time post‐infection and post‐vaccination. Results: One hundred twenty‐four residents and 28 staff underwent saliva serologic testing on one or more survey visits. Over three surveys, the SARS‐CoV‐2 seroprevalence at the facility was 49%, 64%, and 81%, respectively. IgG to S, RBD, and N Antigens all increased post infection. Post vaccination, the infection naïve group did not have a detectable N IgG level, and N IgG levels for the previously infected did not increase post vaccination ( p  < 0.001). Fully vaccinated subjects with prior COVID‐19 infection had significantly higher RBD and S IgG responses compared with those who were infection‐naïve prior to vaccination ( p  < 0.001 for both). Conclusions: Positive SARS‐COV‐2 IgG in saliva was concordant with prior infection (Anti N, S, RBD) and vaccination (Anti S, RBD) and remained above positivity threshold for up to 9 months from infection. Salivary sampling is a non‐invasive method of tracking immunity and differentiating between prior infection and vaccination to inform the need for boosters in LTC residents and staff.